Effect of preoperative right ventricular dysfunction and dilatation on survival after left ventricular surgical restoration - Abdelhameed Elsayed; Murtadha H. Alawami; Ismail M. Elnaggar; Tamer N. Mohamed; Musab Kiddo; Mostafa A. Shalaby; Khaled A. Alotaibi; Amr A. Arafat (The Cardiothoracic Surgeon)
Abstract Background This study investigated the impact of preoperative right ventricular (RV) dysfunction and dilatation on survival outcomes following left ventricular surgical restoration (LVSR) in patients with ischemic cardiomyopathy. A retrospective analysis was conducted on 137 patients who underwent LVSR between 2009 and 2021. Results The results indicated that hospital mortality was significantly associated with older age [OR, 1.10; P = 0.01], higher EuroSCORE II [OR, 1.08, P = 0.03], recent myocardial infarction [OR, 4.24, P = 0.02], lower creatinine clearance [OR, 0.97, P = 0.02], and left ventricle longitudinal [OR, 0.95, P < 0.01] and transverse diameter [OR, 0.95; P < 0.01]. Although RV dysfunction alone did not significantly impact survival (log-rank P = 0.48), a trend toward lower survival rates was observed in patients with concurrent RV dilatation and dysfunction (log-rank P = 0.08). Long-term follow-up revealed no significant reduction in RV diameter after surgery. Multivariable analysis revealed that EuroSCORE II [HR, 1.05; P < 0.01], atrial fibrillation [HR, 3.34; P < 0.01], left ventricular longitudinal diameter [HR, 0.97; P < 0.01], and right ventricular basal diameter [HR, 1.06, P < 0.01] were independent predictors of long-term mortality. Conclusions This study underscores the importance of comprehensive preoperative evaluation of RV dimensions and function in predicting outcomes after LVSR, emphasizing the need for tailored management strategies for patients with RV abnormalities.